2015
DOI: 10.1126/science.aaa2618
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of endogenous gene silencing by bidirectional cytoplasmic RNA decay in Arabidopsis

Abstract: Plant immunity against foreign gene invasion takes advantage of posttranscriptional gene silencing (PTGS). How plants elaborately avert inappropriate PTGS of endogenous coding genes remains unclear. We demonstrate in Arabidopsis that both 5'-3' and 3'-5' cytoplasmic RNA decay pathways act as repressors of transgene and endogenous PTGS. Disruption of bidirectional cytoplasmic RNA decay leads to pleiotropic developmental defects and drastic transcriptomic alterations, which are substantially rescued by PTGS muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
196
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(212 citation statements)
references
References 44 publications
9
196
0
7
Order By: Relevance
“…8, C and F), but were excluded from the nuclei. Cytoplasmic localization of AtSKI2 and AtSKI3, consistent with their roles as auxiliary factors required for exosomal activities in the cytoplasm, has been demonstrated previously (Zhang et al, 2015;Yu et al, 2015), but not their presence in the cytoplasmic granules shown here. This suggests the possibility that one or more activities of the AtSKI proteins might require their association into processing bodies (P bodies), cytoplasmic protein complexes known to be involved in degradation and translational arrest of mRNA (Maldonado-Bonilla, 2014).…”
Section: Atski3 and Atski2 Are Localized To The Cytoplasm And Cytoplasupporting
confidence: 56%
See 2 more Smart Citations
“…8, C and F), but were excluded from the nuclei. Cytoplasmic localization of AtSKI2 and AtSKI3, consistent with their roles as auxiliary factors required for exosomal activities in the cytoplasm, has been demonstrated previously (Zhang et al, 2015;Yu et al, 2015), but not their presence in the cytoplasmic granules shown here. This suggests the possibility that one or more activities of the AtSKI proteins might require their association into processing bodies (P bodies), cytoplasmic protein complexes known to be involved in degradation and translational arrest of mRNA (Maldonado-Bonilla, 2014).…”
Section: Atski3 and Atski2 Are Localized To The Cytoplasm And Cytoplasupporting
confidence: 56%
“…In contrast, the N terminus of ScSKI2 that is necessary and sufficient for interaction with ScSKI3 and ScSKI8 in yeast does not exhibit significant homology with the Arabidopsis AtSKI2. This does not, however, preclude successful interactions of AtSKI2 with AtSKI3 and AtSKI8 subunits as demonstrated by pull-down experiments in Arabidopsis (Dorcey et al, 2012;Zhang et al, 2015). It is well-documented that a third component of the SKI complex, named SKI8, is indispensable for the cytoplasmic functions of the exosome (Brown et al, 2000;Orban and Izaurralde, 2005;Dorcey et al, 2012).…”
Section: War7 Is Atski2 the Putative Helicase Of The Ski Complexmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar to most miRNAs, 21-nucleotide ta-siRNAs associate with AGO1 to guide cleavage of homologous mRNAs. RNA quality control siRNAs (rqc-siRNAs) and coding transcript siRNAs (ct-siRNAs) derive from the aberrant forms of mRNAs encoded by protein-coding genes, which are converted into dsRNA by cellular RNA-dependent RNA polymerases (RDR) when decapping activity or 5-to-39 and 39-to-59 RNA decay is impaired (Martínez de Alba et al, 2015;Zhang et al, 2015). Virus-activated siRNAs (vasiRNAs) are produced from mRNAs encoded by proteincoding genes, which are converted into dsRNA, mostly by RDR1, when plants are infected by viruses (Cao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Zhang et al indicates that removal of aberrant transcripts by the RNA decay pathway is the key [4].…”
mentioning
confidence: 99%